Determination and Difference Analysis of Phenolic Compounds in Smokers' Saliva and Mainstream Smoke. (29th September 2022) - Si, Xiaoxi; Yang, Jianyun; Zhang, Fengmei; Zhu, Ruizhi; Liu, Chunbo; Jiang, Wei; Shen, Qingpeng; He, Pei; Tang, Shiyun; Li, Zhenjie; Liu, Zhihua; You, Junheng; et al.
Abstract : To study the differences in phenolic compounds between tobacco smokers' saliva and mainstream smoke, a method was developed for the analysis of 12 phenolic compounds in saliva and mainstream smoke based on ultrahigh-performance liquid chromatography with fluorescence detection (UPLC-FLD). The contents and distributions of phenolic compounds in tobacco smokers' saliva and mainstream smoke were compared. The results were as follows: (1) Phenolic compounds were quantitatively analyzed by the internal standard method using 4-fluorophenol as an internal standard. For smokers' saliva samples, the limits of quantification (LOQs) ranged from 2.2 to 19.1 μ g/L, and the recoveries were from 80.2% to 119.2% at the three spiked levels. For mainstream smoke samples, the LOQs ranged from 0.03 to 0.26 μ g/cig, and the recoveries ranged from 84.9% to 107.0% at the three spiked levels. (2) The contents of phenolic compounds from 14 cigarettes in mainstream smoke and smokers' saliva were determined. In mainstream smoking, the main phenolic compounds were hydroquinone, catechol, phenol, meta - and para -Cresol, and o -methylhydroquinone. In smokers' saliva, the main phenolic compounds were phenol and meta - and para -Cresol and the contents of phenolic compounds in smokers' saliva from different cigarettes were significantly different. (3) The content distribution patterns of phenolic compounds in smokers' saliva differed from those in mainstream smoke. The predominant phenolic compound in mainstream smoke was dihydroxybenzene, while monophenols predominated in smokers' saliva. (4) The contents of phenolic compounds from five kinds of cigarettes were analyzed in the saliva of different smokers using principal component analysis, which indicated that cigarettes with different sensory effects were clearly distinguished by differences in the contents of phenolic compounds in saliva.